استخدام التعليم الإلكتروني في عملية التعليم بالجامعات والمدارس - Badruzzaman, Badruzzaman (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2021)
To conduct the education process during the Corona pandemic, universities and schools benefited from educational technology. This research aims to identify the benefit of educational technology, the so-called e-learning, in the education process. As for the method of this research, it is a descriptive and analytical approach when the researcher analyzes the various teory related to e-learning in the education process. The results of the research are that e-learning helps the teacher and students in the education process during the Corona pandemic. E-learning does not eliminate the role of the teacher, but rather his role becomes more important.